2015
DOI: 10.1007/s00436-015-4687-5
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory nematodes in cat populations of Italy

Abstract: The occurrence of common respiratory parasites of domestic cats (the metastrongyloid "cat lungworm" Aelurostrongylus abstrusus and the trichuroid Capillaria aerophila) and of neglected respiratory nematodes of felids (Troglostrongylus brevior, Angiostrongylus chabaudi and Oslerus rostratus) was here evaluated in two and three geographical sites of Northern and Central Italy, respectively. In 2014-2015, individual fecal samples of 868 domestic cats were examined microscopically and genetically, and epidemiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 42 publications
2
52
0
1
Order By: Relevance
“…These results are in accord with other similar studies that recently have reported, prevalence values of A. abstrusus infection in cats from Romanian varying from 5.6% (Mircean et al, 2010) to 14.16% (Giannelli et al, 2017). When comparing with other European countries, large variation for the prevalence rates of A. abstrusus are found, with values from 2% (Cyprus; Diakou et al, 2017), 8.3% in Denmark (Hansen et al, 2017) up to 17% in Italy (Di Cesare et al, 2015) or 50% in feral cats from Albany (Pennisi et al, 2015). A recent studies in 12 European countries performed by Giannelli et al (2017) showed that of the lungworm species, A. abstrusus was the most frequent (78.10%), while other lungworm species were found in lower prevalence, such as Troglostrongylus brevior (19.5%), Eucoleus aerophilus (14.8%) or Oslerus rostratus (3.8%).…”
Section: Resultssupporting
confidence: 92%
“…These results are in accord with other similar studies that recently have reported, prevalence values of A. abstrusus infection in cats from Romanian varying from 5.6% (Mircean et al, 2010) to 14.16% (Giannelli et al, 2017). When comparing with other European countries, large variation for the prevalence rates of A. abstrusus are found, with values from 2% (Cyprus; Diakou et al, 2017), 8.3% in Denmark (Hansen et al, 2017) up to 17% in Italy (Di Cesare et al, 2015) or 50% in feral cats from Albany (Pennisi et al, 2015). A recent studies in 12 European countries performed by Giannelli et al (2017) showed that of the lungworm species, A. abstrusus was the most frequent (78.10%), while other lungworm species were found in lower prevalence, such as Troglostrongylus brevior (19.5%), Eucoleus aerophilus (14.8%) or Oslerus rostratus (3.8%).…”
Section: Resultssupporting
confidence: 92%
“…pregnant women and immunocompromised individuals are at high risk of being infected and develop diseases related to feline parasites [1]. Apart from the anecdotal cosmopolitan distribution of the most common feline endoparasitic helminths, like Toxocara cati , Toxascaris leonina , Taenia (Hydatygera) taeniaeformis and Aelurostrongylus abstrusus [2–4], little is known about the status of infection in outdoor cats in Sweden, since they are not routinely tested for parasitic infections. The majority of faecal samples submitted for parasitological examination comes from cats showing clinical signs such as expulsion of helminths and diarrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them, e.g. Troglostrongylus subcrenatus or Oslerus rostratus , still remain of minor and limited relevance under an epizootiological standpoint and are likely to be confined in their wild hosts [ 1 4 ]. Conversely, Troglostrongylus brevior has gained high attention in the past few years, for its clinical relevance, especially in young animals and for an apparent expansion in populations of domestic cats [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%